Drug-herb interactions : selected antihypertensive drugs with Moringa oleifera leaves extract - Endang Kumolosasi,; Cheong, Mandy Li Ching; Nuraina Athira Ahmad Salwanizam,; Nur Shamizah Ainna Muhammad Esham,; Qistina Alyani Ayob,; Ramavisithira Ramasamy,; Harishankari Govindan,; Adyani Md Redzuan,; Malina Jasamai, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Moringa oleifera is a local plant which is commonly used in cooking and as a health supplement. It has been reported to possess blood pressure (BP) lowering effect and little is known about its possible interactions with cardiovascular drugs. This study looked into the possible drug-herb interactions between M. oleifera leaves extract and selected antihypertensive drugs. Ten groups of spontaneously hypertensive rats (SHRs) and one group of normotensive rats (NTs) were administered either M. oleifera extract alone, drugs alone or drugs in combination with M. oleifera extract for 14 days and BP of the rats were measured. Angiotensin converting enzyme (ACE) activity was also determined in vitro and ex vivo. Treated groups were found to produce significant BP reduction on day 15 when compared with the negative control but there was no significance difference when compared with positive controls (drugs alone). M. oleifera extract administered alone significantly reduced BP of SHRs on day 15 and this is comparable with the BP reduction observed when antihypertensive drugs were administered alone. However, no additive effect was observed when drugs were used in combination with M. oleifera extract. Similar results were seen in the in vitro and ex vivo ACE inhibitory activity of M. oleifera extract and enalapril. It can be concluded that there is a possibility of drug-herb interaction between M. oleifera extract and the selected antihypertensive drugs.